1990
DOI: 10.1161/01.str.21.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease in Hong Kong Chinese.

Abstract: Our prospective study of cerebrovascular disease in Hong Kong confirms a previous clinical impression that stroke in the Chinese has a pattern different from that in Caucasians. We studied 540 patients (aged 20-70 years) with stroke. Computed tomography or autopsy was obtained in 86.1% and showed an increase in the proportion with lacunar infarction, striatocapsular infarction, and parenchyma! hemorrhage relative to the frequencies in Caucasians. This increase in the incidence of cerebral hemorrhage occurs not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Thus, in the study it was found that in both gender the haemorrhagic was more common than ischaemic stroke. Similar results were observed in the study done previously in Hongkong Chinese by Haung et al [16].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, in the study it was found that in both gender the haemorrhagic was more common than ischaemic stroke. Similar results were observed in the study done previously in Hongkong Chinese by Haung et al [16].…”
Section: Discussionsupporting
confidence: 93%
“…The pattern of strokes in Saudis was more like that in Europeans 13-15 -22 -25 than like that in Chinese 26 and Japanese.…”
Section: Discussionmentioning
confidence: 78%
“…[7][8][9][10][11][12][13][14][15][16] Previous studies in China, Hong Kong, Taiwan, and Japan generally found that 23% to 52.2% of strokes were hemorrhagic, [3][4][5][6][21][22][23][24][25] in contrast to only 9% to 18% in whites. [7][8][9][10][11][12][13][14][15][16] In the present study, 29.6% of stroke cases overall in 2000 were hemorrhagic in Chinese populations, which supported the above idea that an ethnic difference existed between Eastern and Western populations.…”
Section: Stroke Subtypes In Chinese Populations Compared With Westernmentioning
confidence: 99%